PERBANDINGAN JUMLAH KOLONI BAKTERI SEBELUM DAN SESUDAH PENGGUNAAN OBAT KUMUR YANG MENGANDUNG CETYLPYRIDINIUM CHLORIDE ANTARA KELOMPOK PEROKOK DAN BUKAN PEROKOK - IKCHAN MALIK NAPITUPULU; ANNISA . (LP2MTBM MAKARIOZ, 2021)
Human oral cavity is found by a variety of living and settled microorganisms. Some microorganisms are normal flora and arepathogenic if the amount is excessive in the mouth. This can be influenced by environmental factors such as smoking.Smoking can cause pathological effects in the oral cavity. The heat produced by cigarettes can cause vascularity and salivasecretion so that bacteria easily colonize. Cetylpyridinium chloride is a mouthwash that has the ability to control the numberof bacteria in the mouth. Cetylpyridinium chloride has a broad-spectrum antibacterial effect that is bactericidal capable ofattacking Gram- positive and Gram-negative bacteria. To compare the number of bacterial colonies before and after the useof mouthwash containing cetylpyridinium chloride between smokers and nonsmokers. This study used an experimentalmethod with a pretest and posttest controlled group research design. The analysis used in this study is the Mann-Whitneytest. The study showed that the average number of bacterial colonies before using cetylpyridinium chloride was more in thesmoker group than in the nonsmoker group with a p value = 0,000. The number of bacterial colonies was reduced after usingcetylpyridinium chloride, where the average number of bacterial colonies in the smokers group was higher than the smokersgroup with a p value of 0.001. There is a difference between the number of bacterial colonies before and after the use ofmouthwash containing cetylpyridinium chloride between smokers and nonsmokers.